Peran Guru Dalam Meningkatkan Minat Baca Peserta Didik Melalui Program Literasi Baca Di Kelas Va SD Muhammadiyah Pahandut Palangka Raya - Ariska; Mardiana, Dina (Pusat Kajian Bahasa Daerah & Budaya, 2024)
Reading plays an important role in the development of critical thinking skill, analytical ability, and creativity. Therefore, reading interest must be cultivated from an early age so that it becomes a good habit in daily life. In fostering reading interest, the role of teachers is very crucial. Teachers must be able to create literacy programs that are interesting and in accordance with the needs of students so that their interest in reading can be increased. This study aims to determine the role of teachers in increasing students' interest in reading through reading literacy program in the elementary school level. This study uses a descriptive qualitative approach. The subjects of this study are class V-A teachers and class V-A students at SD Muhammadiyah Pahandut Palangka Raya. The data in this study was collected through three techniques, namely observation, interviews, and documentation. Meanwhile, data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The results of the study show that there are several factors that affect students' interest in reading, both supporting and inhibiting factors. Supporting factors include adequate facilities and infrastructure, attractive literacy programs, and support from teachers and schools. Inhibiting factors include low interest in reading, lack of support from family, and interference from technology. Although the literacy program has been well implemented, there are still several challenges faced, such as differences in interest and reading ability among students, limited time owned by teachers, and limited reading materials available at school.